Le riviste di Umberto Notari (1903-1922): cultura visiva a Milano tra Futurismo e Novecento (ACME, 2023)
Aim of the study is to outline the yet understudied editorial activity of Umberto Notari through the examination of several magazines founded in Milan between 1903 and 1917: il «Verde e Azzurro», «La Giovane Italia», «Gli Avvenimenti» and «Le Industrie Italiane Illustrate». In addition to tracing the collaborations with members of Futurism and of the Novecento group, the analysis of these materials shows to what extent Notari used his journals to develop pioneering advertising, mass communication and consensus-building strategies, which had many reflections in contemporary visual culture.